Tensile and flexural behaviors of connections between steel beam and concrete-encased-and-filled steel tube column. (15th May 2022) - Lee, Ho-Jun; Park, Hong-Gun; Choi, In-Rak; Hwang, Hyeon-Jong
Abstract: Concrete-encased-and-filled steel tube (CEFT) columns with a circular tube section can be potentially used for hollow precast concrete (PC) constructions, in which thin PC encasement is used to reduce the lifting weight of a large PC column. In the present study, connection methods were studied for steel beam-CEFT column joints with the thin concrete encasement. Two sets of testing were performed focusing on the local behavior of the connection: 1) monotonic tension test for beam flange-column connections, and 2) cyclic loading test for beam-column joints. In the first test, the local out-of-plane behavior of the flange plate-tube connections and the associated damage mode of the concrete encasement were identified. The load-deformation relationships of the test specimens were evaluated by nonlinear finite element analysis. Based on the results, exterior beam-column joint specimens were designed, and the flexural behavior of the connections was verified under cyclic loading. The joint specimens were strengthened with connection methods such as tension bars, thick steel tube, and vertical continuity plate, inducing the beam failure. In particular, the thick tube and vertical continuity plate were effective in restraining the concrete damage. The tensile and flexural strengths of the test specimens were evaluated using design equations. Highlights: Potential connection methods studied for steel beam-CEFT column joints with thin concrete encasement. Local out-of-plane behavior of beam flange-column connections investigated by monotonic tension test. Flexural behavior of the connections verified by cyclic loading test of beam-column joints. Test results evaluated using finite element model and design equations.